-24=j/6-27

Simple and best practice solution for -24=j/6-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24=j/6-27 equation:



-24=j/6-27
We move all terms to the left:
-24-(j/6-27)=0
We get rid of parentheses
-j/6+27-24=0
We multiply all the terms by the denominator
-j+27*6-24*6=0
We add all the numbers together, and all the variables
-1j+18=0
We move all terms containing j to the left, all other terms to the right
-j=-18
j=-18/-1
j=+18

See similar equations:

| -3(y+3)=3y+39 | | -16-2x-3x=9 | | 7u=18+4 | | (X)(x+5)=60 | | 62x+2)+12=50 | | 5x+4=-8+2x+21 | | -13=k/2 | | -5y-27=-7(y+5) | | (y+-8)+-1(y+2)=5y | | 15x-10=4x+56 | | -8=w/6-15 | | 10w-15=-6 | | -24-8v=5(v-7)-2 | | 8^5x=32 | | -13+2x+3x=12 | | 16x^2+46x-28=0 | | z^-5z=0 | | 3k–2=4 | | T+2x=180 | | 90=3x+9 | | 57=s-16 | | R(x)=3^2+27/2x^2-6x-8 | | -3x+x-10=4 | | 2+3+3*11=x | | 0.5n+2.8-0.4n=6.2+0.1 | | -3(4t-5)+9t=3t-2 | | 8n=-136 | | 12-11y=5+7 | | -4(5t-4)+5t=6t-7 | | 2(-7x-8=-16+3 | | 7y-5y=8 | | 10-3b-3/4=b+5/2 |

Equations solver categories